Bone morphogenetic protein signaling promotes tumorigenesis in a murine model of high-grade glioma. Issue 7 (18th December 2015) - Hover, Laura D.; Owens, Philip; Munden, Alexander L.; Wang, Jialiang; Chambless, Lola B.; Hopkins, Corey R.; Hong, Charles C.; Moses, Harold L.; Abel, Ty W.
Abstract: Background: Improved therapies for high-grade glioma (HGG) are urgently needed as the median survival for grade IV gliomas is only 15 months. Bone morphogenetic protein (BMP) signaling plays critical and complex roles in many types of cancer, including glioma, with most of the recently published work focusing on BMP-mediated regulation of glioma stem cells (GSCs). We hypothesized that BMP signaling may be an important modulator of tumorigenic properties in glioma cells outside of the GSC compartment. Methods: We used a human HGG tissue microarray and performed immunohistochemistry for phospho-Smads1, 5, 8. To examine the role of BMP signaling in tumorigenic astrocytes, transgenic mice were used to delete the BMP type IA receptor ( Bmpr1a ) and generate astrocytes transformed with oncogenic Ras and homozygous deletion of p53. The cells were transplanted orthotopically into immunocompetent adult host mice. Results: First we established that BMP signaling is active within the vast majority of HGG tumor cells. Mice implanted with BMPR1a-knockout transformed astrocytes showed an increase in median survival compared with mice that received BMPR1a-intact transformed astrocytes (52.5 vs 16 days). In vitro analysis showed that deletion of BMPR1a in oncogenic astrocytes resulted in decreased proliferation, decreased invasion, decreased migration, and increased expression of stemness markers. In addition, inhibition of BMP signaling in murine cells and astrocytoma cells with a small molecule BMP receptor kinase inhibitor resulted in similar tumor suppressive effects in vitro. Conclusion: BMP inhibition may represent a viable therapeutic approach in adult HGG.